Karakteristik dan eksistensi pekerja sektor informal di Kota Makassar - Andi Samsir; Abdul Rahman (Seminar Nasional LP2M UNM, 2019)
This study aims to: 1) Know the characteristics of street vendors seen from the socio-economic aspects of the city of Makassar; 2) Knowing and analyzing the influence of Age on street vendor income in Makassar City; 3) Knowing and analyzing the influence of the duration of the business on street income in Makassar City; 4) Knowing and analyzing the types of products that differentiate street vendors' income in Makassar City and 5) Knowing and analyzing Education Levels that distinguish street income in Makassar City. The study was conducted using a survey research design. This research was conducted in Makassar City. The population in this study were all street vendors. The sampling technique uses simple random sampling, which is used as a sample of 93 people. The technique of collecting data usesa a questionnaire. The analytical method used is descriptive analysis and multiple linear regression. The results of this study indicate: 1) The revenue aspect that street vendor income is still below the Makassar City UMP. the age level shows that the average is old, indicating that most traders are traders who have long experience. So of course they already have enough experience and skills in running their business, but their education level is still relatively low. 2) Age and duration of business influence and significantly affect the level of income of street vendors in the city of Makassar. 3) There are differences in income between food traders and non-food street vendors in the city of Makassar. 4) The level of education has no effect on street vendors in the city of Makassar. 5) Age, length of business, type of merchandise, and level of education together have a significant effect on street vendors in the city of Makassar